Rescue of Jews - Sakaitė, Viktorija (Genocidas ir rezistencija, 1998)
In this article, the author analyses what were the reasons behind Jewish rescue undertaken by Lithuanians. The reasons for the rescue were various: political or situational, social, personal, or conspiratorial, diplomatic, or territorial, as well as other reasons that are difficult to classify, but are mainly subjective. Many different stories are told about the rescue of Jews.
Keywords: German occupation; Holocaust; Jew; jewish redeemers